ANALISIS SILDENAFIL SITRAT DALAM JAMU KUAT DI KECAMATAN BOGOR BARAT DAN TANAH SAREAL DENGAN MENGGUNAKAN KROMATOGRAFI CAIR SPEKTROMETRI MASSA - Triyani Sumiati; Bina Lohita Sari; Nurtiyah (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2017)
Herbal medicineisthe treatment of choicebecause ofmerit in maintainingthe health ofthe peopleof the human body. Strongherbal medicineisherbal medicinethat isefficacious asstaminaandvitality ofman, but in its developmentpuritypowerfulherbsare addedsildenafilcitratebyparties who are notresponsible. This study was adescriptiveanalysis ofexperimentaldesign. Analysis of sildenafilcitrate compounds using Thin Layer Chromatography (TLC) and Liquid Chromatography Mass Spectrometry (LC-MS) were sampled in two districts, namely sub-district, Bogor Barat and Tanah Sareal thus obtained 32 samples, of which 18 samples of Bogor Barat coded A and 14 samples from Tanah Sareal coded B. TLC results were eluted at Silica gel 60 F254 with eluent methanol:chloroform (4:1), there were 5 samples showed close Rf value standard sildenafil citrate is 0.83, the sample code A4 value of Rf 0.84, A13 Rf value of 0.84, A17 Rf value of 0.83, B11 Rf value of 0.83, and B14 Rf value of 0.84. Results LC-MS where separation using column Phenomenex Synergi Fusion RP-100A, the pumping system with a mobile phase gradient of 0.2 M ammonium acetate pH 7 in water and 0.2 M ammonium acetate pH 7 in acetonitrile, was obtained the samples for A4, A13, A17, B11 dan B14 amounted to 198.01; 1734.14; 226.00; 156.77; 443.87 μg/kg